2003
DOI: 10.1177/0022427803256071
|View full text |Cite
|
Sign up to set email alerts
|

Self-Control, Social Consequences, and Criminal Behavior: Street Youth and the General Theory of Crime

Abstract: Using a sample of 400 homeless street youth, this article examines the role that self-control plays in the generation of crime and drug use as well as its link to negative social consequences. It also explores if these social consequences are themselves related to crime as predicted in strain and differential association theory, or if their impact is eliminated by the presence of low self-control. The results reveal that low self-control predicts a range of criminal behaviors as well as drug use. Consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
161
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(180 citation statements)
references
References 29 publications
(66 reference statements)
14
161
3
2
Order By: Relevance
“…Even though numerous homeless young adults are likely to be in a "survival" mind set where breaking rules and not concerning themselves with who gets hurt in the process (i.e., high deviant beliefs), which may be something many of these young adults do to make it through the day unscathed, such deviant beliefs serve to increase their chances of perpetrating crime and using drugs. This is consistent with prior research, which finds that those with lower self-control or high deviant attitudes (Baron, 2003(Baron, , 2009Pratt & Cullen, 2000) are more likely to participate in crime and use drugs (Baron, 2003). It is possible that when confronted with unjust or severe strains, young people with higher deviant beliefs may be more likely to retaliate physically and use other deviant methods of coping (Agnew, 2006) such as illicit drug use and property crime to cope with both distal (e.g., child abuse) and proximal (e.g., stressors of street life) strains.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Even though numerous homeless young adults are likely to be in a "survival" mind set where breaking rules and not concerning themselves with who gets hurt in the process (i.e., high deviant beliefs), which may be something many of these young adults do to make it through the day unscathed, such deviant beliefs serve to increase their chances of perpetrating crime and using drugs. This is consistent with prior research, which finds that those with lower self-control or high deviant attitudes (Baron, 2003(Baron, , 2009Pratt & Cullen, 2000) are more likely to participate in crime and use drugs (Baron, 2003). It is possible that when confronted with unjust or severe strains, young people with higher deviant beliefs may be more likely to retaliate physically and use other deviant methods of coping (Agnew, 2006) such as illicit drug use and property crime to cope with both distal (e.g., child abuse) and proximal (e.g., stressors of street life) strains.…”
Section: Discussionsupporting
confidence: 92%
“…Baron (1997) found that the more offending behaviors in which male street youth engaged (e.g., robbery, assaults), the greater their risk for violent and/or property victimization. Finally, homeless youth with deviant values are more likely to engage in property and violent crime (Baron, 2003(Baron, , 2009). …”
Section: Criminal Offending and Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Our research provides support for the argument that stable individual propensity, along with family, peers, and street situational risk factors, should be taken into account in explaining delinquent behavior and crime (Baron, 2003;Hagan & McCarthy, 1997). Consistent with previous literature (Hinshaw et al, 1993;Moffitt, 1993aMoffitt, , 1993bMoffitt et 1175Moffitt et al, 1996Patterson & Yoerger, 1997), adolescents with childhood conduct problems exhibit an elevated level of delinquent behavior.…”
Section: Discussionsupporting
confidence: 72%
“…We located only two studies that examined effects of individual propensity on street delinquent behavior and crime. S. Baron (2003) found some evidence that homeless youth with low self-control reported an elevated level of involvement with a series of criminal behaviors and drug use. Those with low self-control were also more likely to have other negative social characteristics such as having deviant peers and deviant values, to be unemployed for longer periods of time, and to be homeless for greater periods of time.…”
Section: Onset Of CD and Deviant Survival Strategies Among Homeless Amentioning
confidence: 99%